Biology and Management of European Earwig in Orchards and Vineyards. (25th June 2019) - Orpet, Robert J; Crowder, David W; Jones, Vincent P
Abstract: European earwig, Forficula auricularia L. (Dermaptera: Forficulidae), is an omnivore found in fruit orchards and vineyards worldwide. Earwigs are predators in many crop systems, but may be pests in others. To address uncertainty regarding the pest status of European earwig, we review its biology, effects in fruit agroecosystems, and management. Current evidence suggests that European earwigs generally have a net positive role in apple and pear orchards, where they consume pests and rarely damage fruit. European earwigs probably have a net negative role in stone fruits, which are soft and susceptible to earwig damage. The net positive or negative role of European earwig in citrus, grape, and kiwi is not clear because there is limited information on their ability to damage these fruits. Management of European earwig involves pesticide sprays or tillage to suppress vulnerable life stages, or inoculative releases to increase earwig populations. Greater appreciation of European earwigs as biological control agents may decrease insecticide use and improve pest suppression.